The impact of demographic change on spousal caregiving and future gaps in long-term care: Microsimulation projections for Austria and Italy - Philipp Warum; Fabrizio Culotta; Ulrike Famira-Mühlberger; Thomas Horvath; Thomas Leoni; Pauline Pohl; Martin Spielauer (Austrian Institute of Economic Research (WIFO), 2025)
As populations age, the sustainability of long-term care systems increasingly depends on the availability of informal care, particularly from partners. This paper addresses the question of how much care we may expect partners to provide in the future by projecting demand for long-term care (LTC), the care supply mix based on current patterns, and the resulting care gaps up to 2070. Using a comparative dynamic microsimulation model, we contrast the results for Austria and Italy, two countries at very different stages in the ageing process and with pronounced institutional differences. Our results suggest that delayed widowhood due to improvements in mortality is a mitigating factor for the increased need for formal care in ageing societies, although it can only offset this increase to a limited extent. Even under optimistic assumptions, potential care gaps substantially increase in both countries, primarily due to demographic change. The size of these gaps is influenced by institutional settings, partnership patterns and gains in longevity, but no scenario reverses the overall upward trend. These findings emphasize the need for comprehensive LTC reforms that extend beyond merely promoting informal care and highlight the necessity for substantial investment in formal care infrastructure.
Keywords: C53; I11; J14; 330; population ageing; long-term care; spousal caregiving; care gap; projections; dynamic microsimulation